Polymeric Membranes Incorporated With ZnO Nanoparticles for Membrane Fouling Mitigation: A Brief Review - Shen, Liguo; Huang, Zhengyi; Liu, Ying; Li, Renjie; Xu, Yanchao; Jakaj, Gjon; Lin, Hongjun (Frontiers in Chemistry, 2020)
Due to the flexibility of operation, high removal ability and economic cost, separation membranes have proved to be one of the most significant technologies in various aspects including water treatment. However, membrane fouling has been a predominant obstacle that severely limits the growth of the membrane industry. To mitigate membrane fouling, researchers have carried out several modification strategies including the incorporation of hydrophilic inorganic components. ZnO nanoparticles, known as a low cost, environment-friendly and hydrophilic inorganic material, have been used by worldwide researchers. As claimed by the scientific literatures, ZnO nanoparticles can not only endow the polymeric membranes with antifouling performance but also can supply a photocatalytic self-cleaning ability. Therefore, polymer-ZnO composite membranes were considered to be an attractive hot topic in membrane technology. In the last decades, it has been significantly matured by a large mass of literature reports. The current review highlights the latest findings in polymeric membranes incorporated with ZnO nanoparticles for membrane fouling mitigation. The membrane fouling, ZnO nanoparticles and modification technology were introduced in the first three sections. Particularly, the review makes a summary of the reports of PVDF-ZnO composite membranes, PES-ZnO composite membranes and other composite membranes incorporated with ZnO nanoparticles. This review further points out several crucial topics for the future development of polymer-ZnO composite membranes.